Amalan Komunikasi Dan Kesannya Terhadap Pencapaian Pelaksanaan Tugas Dalam Tentera Laut DiRaja Malaysia - Lt. Kdr. Mohd. Arif, Ahmad (2001)
Good communication practice is important for effective communication in the organization in achieving its mission and vision. Communication is rather complex due to the diversification of the human characters. Communication practice must be emphasized in achieving the organization's aim through the individual job performance. This research focused on communication practices for Royal Malaysian Navy (RMN) personnel from the rank of Commander and below which represent 99 percent of the whole RMN strength with regard to the job performance. The research intend to answer the questions whether different demographic factors in communication significantly affected the job performance, the correlation between independent variables of communication practices namely the frequency of communication, the mode, communication direction and the communication content with the dependent variable of job performance and to identify the strength of relationship between independent and dependent variables. The research was conducted on 210 respondents with the rank of Commander and below selected by stratified random sampling method from the RMN shore establishments and ship based in Lumut, Perak. The research found that there are differences in communication practices of different demographic groups with regard to the job performance. There are significant relationships between the frequency of communication, the communication direction and the communication content with the job performance. 27.7 percent of job performance variation is influenced by the communication direction and communication content. It is concluded that the research has answered all the questions pertaining to the communication practices in RMN and its effect on the job performance through quantitative research and hypothesis testing.